The Symptoms of Trauma Scale (SOTS): Psychometric evaluation and gender differences with adults diagnosed with serious mental illness. Issue 4 (8th August 2017) - Ford, Julian D.; Schneeberger, Andres R.; Komarovskaya, Irina; Muenzenmaier, Kristina; Castille, Dorothy; Opler, Lewis A.; Link, Bruce
ABSTRACT: A new clinician rating measure, the Symptoms of Trauma Scale (SOTS), was administered to adult psychiatric outpatients (46 men, 47 women) with severe mental illness who reported a history of trauma exposure and had recently been discharged from inpatient psychiatric treatment. SOTS composite severity scores for Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, and Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, posttraumatic stress disorder (PTSD), complex PTSD (cPTSD), and total PTSD/cPTSD severity had acceptable internal consistency reliability. SOTS scores' construct and convergent validity was supported by correlations with self-report measures of childhood and adult trauma history and PTSD, dissociation, and anger symptoms. For men, SOTS scores were associated with childhood sexual and emotional abuse and self-reported anger problems, whereas for women SOTS scores were most consistently and strongly associated with childhood family adversity and self-reported PTSD symptoms. Results provide preliminary support for the reliability and validity of the SOTS with adults with severe mental illness and suggest directions for replication, measure refinement, and research on gender differences.